Women in IT-ITES Industries: Their Coping Styles and Quality of Work Life - Bharathi; Kavya (SDMIMD Journal of Management, 2021)
Women have chosen to establish their names in the competitive globe along with being good home-makers. Information Technology-Information Technology Enabled Services (IT-ITES) industries have helped women to establish their names in the competitive globe along with being good home-makers. With increasing responsibilities, women have been subjected to increasing stress. Women tend to use different coping styles to protect themselves against stress. Not all coping mechanisms are healthy. Meanwhile attention needs to be paid on the quality of their work life, as it's a very competitive and dynamic industry. This study emphasizes on the different coping styles adopted by the women employees, their quality of work life and the relationship between these two variables. The research design used for the study is descriptive design. The researcher adopted convenient sampling technique to collect data from 307 women employees representing six IT-ITES companies in Bangalore city. The study revealed that the ‘distractive positive' method of coping style was the most widely used by the women employees. The ‘quality of work life' of these women employees was on the higher side. The results also showed that there is a significant relationship between coping style and quality of work life.